2005
DOI: 10.1105/tpc.105.034900
|View full text |Cite
|
Sign up to set email alerts
|

Diacidic Motifs Influence the Export of Transmembrane Proteins from the Endoplasmic Reticulum in Plant Cells

Abstract: In yeast and mammals, amino acid motifs in the cytosolic tails of transmembrane domains play a role in protein trafficking by facilitating export from the endoplasmic reticulum (ER). However, little is known about ER export signals of membrane proteins in plants. Therefore, we investigated the role of diacidic motifs in the ER export of Golgi-localized membrane proteins. We show that diacidic motifs perform a significant function in the export of transmembrane proteins to the Golgi apparatus, as mutations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 67 publications
9
100
0
Order By: Relevance
“…Our findings provide evidence for increased recruitment of Sec24 to ERES upon coexpression of the Golgi membrane markers ERD2-GFP or TMcCCASP (Hanton et al, 2005b). Mutagenesis experiments revealed that this effect is strictly dependent on the diacidic ER export signal DXE (Hanton et al, 2005b).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Our findings provide evidence for increased recruitment of Sec24 to ERES upon coexpression of the Golgi membrane markers ERD2-GFP or TMcCCASP (Hanton et al, 2005b). Mutagenesis experiments revealed that this effect is strictly dependent on the diacidic ER export signal DXE (Hanton et al, 2005b).…”
mentioning
confidence: 58%
“…An ER export signal for ERD2 has yet to be discovered, but it has been shown in yeast that Sec24 can interact with diacidic motifs in the cytosolic tails of membrane proteins (Votsmeier and Gallwitz, 2001). We have previously shown that diacidic export motifs are functional in plants because mutation of these signals strongly reduced the export of different membrane proteins from the ER (Hanton et al, 2005b).…”
Section: Eres Formation and Copii Recruitment To Eres Are Signal Depementioning
confidence: 99%
See 1 more Smart Citation
“…The differential inhibitory effect of AtPRA1.B6 can also be observed if the COPII-dependent exit of cargo proteins from the ER is mediated by multiple pathways. Indeed, certain cargoes, such as GONST1, CASP, and KAT, exit the ER in a sorting signal-dependent manner, whereas a-amylase is secreted from the ER by the default or bulk flow pathway (Denecke et al, 1990;Phillipson et al, 2001;Hanton et al, 2005;Sieben et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the perturbation of the BP-80 route to the vacuole can be monitored by following the relative abundance of the GFP-core on western-blot analyses. In addition, secretory GFP forms bearing a glycosylation peptide, glycosylated GFP, have been shown to be efficiently glycosylated in the plant ER (Batoko et al, 2000;Hanton et al, 2005). Therefore, they can be used as reliable markers to follow protein translocation into the ER and protein progression through the Golgi apparatus via endoglycosidase (ENDO-H) digestion (Hanton et al, 2007b).…”
Section: Gfp For Quantitative Analysesmentioning
confidence: 99%